Axial Disease in Psoriatic Arthritis study: defining the clinical and radiographic phenotype of psoriatic spondyloarthritis. Issue 4 (2nd December 2016) - Jadon, Deepak R; Sengupta, Raj; Nightingale, Alison; Lindsay, Mark; Korendowych, Eleanor; Robinson, Graham; Jobling, Amelia; Shaddick, Gavin; Bi, Jing; Winchester, Robert; Giles, Jon T; McHugh, Neil J
Abstract : Objectives: To compare the prevalence, clinical and radiographic characteristics of psoriatic spondyloarthritis (PsSpA) in psoriatic arthritis (PsA), with ankylosing spondylitis (AS). Methods: A prospective single-centre cross-sectional observational study recruited consecutive PsA and AS cases. Participants completed outcome measures, and underwent clinical examination, axial radiographic scoring and HLA- sequencing. Multivariable analyses are presented. Results: The 402 enrolled cases (201 PsA, 201 AS; fulfilling classification criteria for respective conditions) were reclassified based upon radiographic axial disease and psoriasis, as: 118 PsSpA, 127 peripheral-only PsA (pPsA), and 157 AS without psoriasis (AS) cases. A significant proportion of patients with radiographic axial disease had PsSpA (118/275; 42.91%), and often had symptomatically silent axial disease (30/118; 25.42%). Modified New York criteria for AS were fulfilled by 48/201 (23.88%) PsA cases, and Classification of Psoriatic Arthritis criteria by 49/201 (24.38%) AS cases. pPsA compared with PsSpA cases had a lower frequency of HLA-B*27 (OR 0.12; 95% CI 0.05 to 0.25). Disease activity, metrology and disability were comparable in PsSpA and AS. A significant proportion of PsSpA cases had spondylitis without sacroiliitis (39/118; 33.05%); they less frequently carried HLA-B*27 (OR 0.11; 95% CI 0.04 to 0.33). Sacroiliac joint complete ankylosis (adjusted OR, ORadj 2.96; 95% CI 1.42 to 6.15) and bridging syndesmophytes (ORadj 2.78; 95% CI 1.49 to 5.18) were more likely in AS than PsSpA. Radiographic axial disease was more severe in AS than PsSpA (Psoriatic Arthritis Spondylitis Radiology Index Score: adjusted incidence risk ratio 1.13; 95% CI 1.09 to 1.19). Conclusions: In a combined cohort of patients with either PsA or AS from a single centre, 24% fulfilled classification criteria for both conditions. The pattern of axial disease was influenced significantly by the presence of skin psoriasis and HLA-B*27 .